Knowledge graph for integration and quality traceability of agricultural product information - Jing, Rongzhi; Li, Ping (Frontiers in Sustainable Food Systems, 2024)
The quality traceability of agricultural products has become a growing concern for citizens of many countries. It is a complex process involving multiple activities carried out by farmers and other stakeholders who must manage multiple heterogeneous data sources collected and generated through a variety of applications, services and devices. An agricultural product information integration and quality traceability model is proposed based on knowledge graph (KG). Through modeling, extraction, fusion, storage, calculation, reasoning and application of knowledge of agricultural products, KG is constructed to integrate the knowledge of agricultural production and monitoring process. In KG, nodes represent agricultural products and their foods, and their related specific things or their property values, lines connect to the agricultural products, food, and their properties, forming network, each node and the relationship has uniqueness, the KG of agricultural products and food is stored in the Neo4j database in graph structure, which is clear and easy to reuse.The quality tracking of agricultural products and their foods can be conducted through node and path matching in KG. It provides a technical approach for the quality and safety management of agricultural products "from field to Table ".